1988
DOI: 10.1002/cne.902730107
|View full text |Cite
|
Sign up to set email alerts
|

New view of the organization of the pulvinar nucleus in Tupaia as revealed by tectopulvinar and pulvinar‐cortical projections

Abstract: The projections of the superficial layers of the superior colliculus to the pulvinar nucleus in Tupaia were reexamined by injecting WGA-HRP into the tectum. The main result was finding two different patterns of terminations in the pulvinar nucleus: a zone remote from the lateral geniculate nucleus, which occupies the dorsomedial and caudal poles of the pulvinar nucleus, was almost entirely filled with terminals in every case irrespective of the location of the injection site; and a second division of the pulvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(86 citation statements)
references
References 28 publications
6
80
0
Order By: Relevance
“…Both sets of experiments indicate that the caudal pulvinar nucleus is connected with more rostral regions of the temporal cortex, whereas the rostral pulvinar connects to more caudal regions of the temporal cortex. These results corroborate the findings of Luppino et al (1988), who described the distribution of pulvinar cells labeled by retrograde transport following injections in dorsal (Td) and ventral (Tv) subdivisions of the tree shrew temporal cortex, as well as Diamond et al (1970) and who described the distribution of degenerating thalamocortical cells and terminals following cortical or thalamic lesions respectively.…”
Section: Define 2 Temporal Areassupporting
confidence: 90%
See 1 more Smart Citation
“…Both sets of experiments indicate that the caudal pulvinar nucleus is connected with more rostral regions of the temporal cortex, whereas the rostral pulvinar connects to more caudal regions of the temporal cortex. These results corroborate the findings of Luppino et al (1988), who described the distribution of pulvinar cells labeled by retrograde transport following injections in dorsal (Td) and ventral (Tv) subdivisions of the tree shrew temporal cortex, as well as Diamond et al (1970) and who described the distribution of degenerating thalamocortical cells and terminals following cortical or thalamic lesions respectively.…”
Section: Define 2 Temporal Areassupporting
confidence: 90%
“…The tectal projections to these 2 subdivisions are organized differently; those to Pd terminate diffusely, whereas those to Pc terminate in a more spatially precise manner (Luppino et al 1988). In subsequent studies usmg anterograde and retrograde tracing techniques, as well as electron microscopy, we concluded further that although both Pd and Pc receive topographically organized projections from the SC, the Pd receives additional diffuse projections, which possibly arise from wide-ranging axon collaterals of tectopulvinar cells ).…”
Section: Introductionmentioning
confidence: 78%
“…Projections from PC (Lyon et al 2003;Luppino et al 1988) and PD (Luppino et al 1988) to V2 have been previously reported. These two studies used retrograde tracer injections in V2 to identify cell bodies in the thalamus that project to V2.…”
Section: Secondary Visual Pathway Temporal Cortical Areasmentioning
confidence: 94%
“…None of our anterograde injections in the pulvinar nucleus regions PC and PD projected to V2. In reviewing those studies, the lack of PD to V2 projections in the more recent study by Lyon et al (2003) may indicate that the injections by Luppino et al (1988) overran the boundary of V2 to TP (Luppino et al 1998 figure 8) and V2 to TD (Luppino et al 1998 figure 9), so that the cell bodies found in PD came from TP and I or caudal TD.…”
Section: Secondary Visual Pathway Temporal Cortical Areasmentioning
confidence: 99%
“…Luppino et al (1988) first described these projections as "diffuse" and "specific" respectively. By using a combination of anterograde and retrograde tracing techniques, as well as electron microscopy, we concluded that both the Pd and Pc receive topographic (specific)…”
Section: Functional Implicationsmentioning
confidence: 99%